Emotional intelligence and personality traits in high school students: a survey study - Ghazali, Azam; Ashari, Zakiah Mohamad; Hardman, Joanne; Arif, Nur Syahidatun Husna (Institute of Advanced Engineering and Science, 2024)
The capacity to regulate our emotions in unusual circumstances is known as emotional intelligence (EI). EI is now commonly acknowledged as a significant barrier to the performance of students as well as to the big five personality (BFP) of them. In order to find out the effect of EI on individual’s personality, this study was conducted quantitatively to determine i) the level of EI of students in form 2 and 4; ii) gender differences in EI among students in form 2 and 4; and iii) the possibility whether there is a significant relationship between aspects of emotional intelligence and BFP towards form 2 and form 4 students. This study was conducted quantitatively at a Malaysian Secondary School located in Pahang, Malaysia. A set of questionnaires was distributed to 108 respondents at the school. For ethical consideration, the researcher informed the responsible behalf such as regional education department and school and distributed each sample an informed consent form. The findings indicate that self-regulation is the highest level of personality dimension achieved which is m=3.54. On the other hand, there is no significant difference between genders among students in form 2 and 4 affected by EI. Besides, there is a significant relationship between aspects of EI and BFP where the Pearson coefficient, or r-value is 0.674. Future research on interventions that are more appropriate for developing students’ personalities to enhance their EI should be undertaken, according to the implications of this study.